Expression of matrix metalloproteinases 2, 7 and 9 in patients with colorectal cancer - Kostova, Elena; Slaninka Miceska, Maja; Labachevski, Nikola; Jakjovski, Krume; Trojachanec, Jasmina; Atanasovska, Emilija; Janevski, Vlado; Jovanovikj, Rubens; Janevska, Vesna (National Library of Serbia, 2014)
Matrix metalloproteinases (MMPs) are perceived to play a key role in tumor invasion and metastasis by their capacity to degrade basement membranes and extracellular matrix proteins. The aim of this study was to investigate the expressions of MMP-2, MMP-7 and MMP-9 in tumor tissue and their relation to clinicopathologic features in patients with colorectal cancer.